Crowdfunding for Unproven Stem Cell–Based Interventions - Snyder, Jeremy (JAMA, 2018)
This study examines crowdfunding campaigns on GoFundMe and YouCaring sponsored by US-based businesses engaging in direct-to-consumer marketing of stem cell interventions to discover whether the benefits and risks are mentioned in the campaign descriptions.